PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN DISPOSISI MATEMATIS - Paramitha, Ika; Misdalina, Misdalina; Andinasari, Andinasari (JURNAL e-DuMath, 2019)
AbstractThe purpose of this research is to find out whether or not there is an influence oflearning model creative problem solving on the ability of mathematical problem solving and mathematical disposition of students in Palembang 19 Junior High School. This research is an experimental study with the treatment design of Posttest-Only Control Design. The population in this study were all class VII Palembang 19 State Junior High Schools. The cluster sampling technique obtained class VII.1 as an experimental class and class VII.2 as a control class. The experimental class is treated withlearning models creative problem solving, while the control class is treated with conventional learning. Data collection techniques using tests and questionnaires. Data analysis technique uses t test (independent sample t-test). Based on the results of the analysis 1) there is the influence oflearning model creative problem solving on the mathematical problem-solving ability of students of SMP Negeri 19 Palembang. 2) there is the influence of learning models creative problem solving on mathematical dispositions of students of Palembang State 19 Middle School.Keywords: Problem Solving Ability, Creative Problem Solving Learning Model, Mathematical Disposition